A novel hybrid method of LSSVM-GA with multiple stage optimization for electricity price forecasting - Razak I.A.W.A.; Abidin I.Z.; Yap K.S.; Abidin A.A.Z.; Rahman T.K.A.; Nasir M.N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Commerce; Costs; Electric power systems; Forecasting; Genetic algorithms; Optimization; Support vector machines; Accuracy; Electrical power system; Electricity price forecasting; Electricity prices; Least square support vector machines; Multi-stage optimization; Optimized parameter; Parameter selection; Power markets